An Analysis of Slang Found in X Thread By K-Popers - Aulya, Rheyza; Binawan, Heribertus (English Language Education Department, Universitas Kristen Duta Wacana (UKDW), Yogyakarta, Indonesia, 2025)
This research focuses on using slang words in social media X, previously known as Twitter, especially in comments by K-pop fans, known as K-popers. The method used in this research is a qualitative case study, with data collected through participatory observation and content analysis of X comments posted by Kpopers. Wit a tweet on X being the primary data source. The analysis includes identifying the types of slang used and its interpretation within the cultural background according to Allan and Burridge’s theory, as well as a conceptual framework that explains linguistics in aspects of semantics. This research is expected to provide theoretical insights into linguistic dynamics in online communities and practical benefits in understanding how cultural and social identities are constructed and maintained through language.